Hybrid warfare among the other concepts of the modern armed conflicts - Осадча, Я. Д. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The author concerns the most influential concepts of contemporary armed conflicts and analyzes their research potential. Attention is focused on the main thesis of a hybrid war theory. Moreover, the place of the hybrid warfare among similar paradigms was defined. In addition, it was explained why this concept is the best one in studying modern wars.